Can the Paris Deal Boost SDGs Achievement? An Assessment of Climate Mitigation Co-benefits or Side-effects on Poverty and Inequality - Lorenza Campagnolo; Marinella Davide (Fondazione Eni Enrico Mattei (FEEM), 2017)
The paper analyses the synergies and trade-offs between emission reduction policies and sustainable development objectives. Specifically, it provides an ex-ante assessment that the impacts of the Nationally Determined Contributions (NDCs), submitted under the Paris Agreement, will have on the Sustainable Development Goals (SDGs) of poverty eradication (SDG1) and reduced income inequality (SDG10). By combining an empirical analysis with a modelling exercise, the paper estimates the future trends of poverty prevalence and inequality across countries in a reference scenario and under a climate mitigation policy with alternative revenue recycling schemes. Our results suggest that a full implementation of the emission reduction contributions, stated in the NDCs, is projected to slow down the effort to reduce poverty by 2030 (+2% of the population below the poverty line compared to the baseline scenario), especially in countries that have proposed relatively more stringent mitigation targets and suffer higher policy costs. Conversely, countries with a stringent mitigation policy experience a reduction of inequality compared to baseline scenario levels. If financial support for mitigation action in developing countries is provided through an international climate fund, the prevalence of poverty will be slightly reduced at the aggregate level (185,000fewer poor people with respect to the mitigation scenario), but the country-specific effect depends on the relative size of funds flowing to beneficiary countries and on their economic structure.
Keywords: C23; C68; Q56; 330; SDGs; Poverty; Inequality; CGE Model; Mitigation Policy; Paris Agreement